Plants as Antileishmanial Agents: Current Scenario. (5th October 2016) - Ullah, Nazif; Nadhman, Akhtar; Siddiq, Sumaira; Mehwish, Shaila; Islam, Arshad; Jafri, Laila; Hamayun, Muhammad
Abstract : Leishmaniasis is a clinical manifestation caused by the parasites of the genus Leishmania . Plants are reservoirs of bioactive compounds, which are known to be chemically balanced, effective and least injurious as compared with synthetic medicines. The current resistance and the toxic effects of the available drugs have brought the trend to assess the antileishmanial effect of various plant extracts and their purified compound/s, which are summarized in this review. Moreover, it also highlights various traditional remedies used by local healers against leishmaniasis. A systematic cross‐sectional study for antileishmanial activity of natural products was carried out using multiple literature databases. The records retrieved since 2000 till year 2016 were analysed and summarized in the form of comprehensive tables and graphs. Natural products are potential source of new and selective agents that can significantly contribute to primary healthcare and probably are promising substitutes of chemicals for the treatment of protozoan diseases like leishmaniasis. Where the researchers prefer to use alcoholic solvents for the extraction of antileishmanial agents from plants, most of the studies are limited to in vitro conditions majorly on using promastigote forms of Leishmania . Thus, there is a need to carry out such activities in vivo and in host macrophages. Further, there is a need of mechanistic studies that can help taking few of the promising pure compounds to clinical level. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The current resistance and the toxic effects of the available drugs have brought the trend to assess the antileishmanial effect of various plant extracts and their purified compound/s. Natural products are potential source of new and selective agents that can significantly contribute to primary healthcare and probably are promising substitutes of available drugs for the treatment of protozoan diseases like leishmaniasis. However, to develop such compounds as next drug against leishmaniasis, it is very important to test natural agents both in in‐vivo and in host macrophages.